Organisational context and citizenship behaviour: exploring the moderating effects of role ambiguity - Kim, Lian Lee; Low, Guan Tui; Saeed Pahlevan Sharif, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The purpose of this paper is to examine the effect of organisational context on the organisational citizenship behaviour. The study also aimed at finding out the moderating effect of the role ambiguity on the relationship between organisational context (i.e. structure) and the organisational citizenship behaviour. Data from 280 respondents were used in the statistical analysis. Covariance-Based Structural Equation Modelling was used to test the hypotheses. The study revealed that structure has a significant positive effect on organisational citizenship behaviour. The interaction of organisational structure and role ambiguity has a significant positive effect on organisational citizenship behaviour. Statistical analysis confirmed that role ambiguity is a significant moderator of the relationship between organisational structure and organisational citizenship behaviour.